Biogenic Ag–Cu Nanoparticles Synthesized with Extract of Eryngium Billardieri L. and Evaluation of their Anticancer Potential on PC-3 and LNCaP Cancer Cell Lines - Zahra Ebrahim; Ghazaleh Feyzabadi; Nastaran Asghari Moghaddam; Azadeh Mohammadgholi (Advanced Biomedical Research)
Background: The anticancer action of biogenic Ag-Cu nanoparticles (NPs) using Eryngium billardieri against PC-3 and LNCaP cell lines in prostate malignancy was investigated. Materials and Methods: XRD, FTIR, EDAX, FESEM, and TEM were used to illustrate the Ag–Cu NPs. The PC-3 and LNCaP cell lines were used to test the anticancer ability of Ag–Cu NPs. The cytotoxicity was assessed by MMT and flow cytometry. Apoptotic and metastatic-promoting gene expressions were evaluated by real-time PCR. ROS generation was measured. Results: NPs are spherical and their average size was 12 ± 9.7 nanometers. The EDAX result indicated the presence of Ag, Cu, and C. The XRD results revealed the NPs’ crystalline structure. The results demonstrated a remarkable antiproliferative effect of the nanoparticles, with IC50 values of 15.43 μg/mL for PC-3 and 7.64 μg/mL for LNCaP. The Ag–Cu NPs exhibited a tendency to trigger apoptosis. This was confirmed by analyzing apoptosis-related gene expression. The apoptotic influence of Ag–Cu NPs was suggested to be critical when compared to the control and extract-treated groups by the up-regulation of Bcl2-related X (Bax), caspase3, and caspase9, and the down-regulation of Bcl2. Furthermore, Annexin V-FITC/propidium iodide presented a 23.15% and 22.3% apoptotic ratio of PC-3 and LNCaP cells, respectively. Vascular endothelial growth factor (VEGF), and metalloproteinases (MMPs) down-regulation showed that Ag–Cu NPs were hostile to metastasis. Also, ROS generation was estimated at 1261 and 1366 RFU in LNCaP and PC-3 cells treated with green-synthesized Ag–Cu NPs, respectively. Conclusions: The study suggested E. billardieri synthesized Ag–Cu as a potential candidate in prostate cancer therapeutic management.